Tailor-Made Pentablock Copolymer Based Formulation for Sustained Ocular Delivery of Protein Therapeutics. (22nd June 2014) - Patel, Sulabh P.; Vaishya, Ravi; Mishra, Gyan Prakash; Tamboli, Viral; Pal, Dhananjay; Mitra, Ashim K.
Abstract : The objective of this research article is to report the synthesis and evaluation of novel pentablock copolymers for controlled delivery of macromolecules in the treatment of posterior segment diseases. Novel biodegradable PB copolymers were synthesized by sequential ring-opening polymerization. Various ratios and molecular weights of each block (polyglycolic acid, polyethylene glycol, polylactic acid, and polycaprolactone) were selected for synthesis and to optimize release profile of FITC-BSA, IgG, and bevacizumab from nanoparticles (NPs) and thermosensitive gel. NPs were characterized for particle size, polydispersity, entrapment efficiency, and drug loading. In vitro release study of proteins from NPs alone and composite formulation (NPs suspended in thermosensitive gel) was performed. Composite formulations demonstrated no or negligible burst release with continuous near zero-order release in contrast to NPs alone. Hydrodynamic diameter of protein therapeutics and hydrophobicity of PB copolymer exhibited significant effect on entrapment efficiency and in vitro release profile. CD spectroscopy confirmed retention of structural conformation of released protein. Biological activity of released bevacizumab was confirmed by in vitro cell proliferation and cell migration assays. It can be concluded that novel PB polymers can serve a platform for sustained delivery of therapeutic proteins.